2003
DOI: 10.1207/s15327914nc4702_12
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Wheats With High Orthophenolic Content

Abstract: The purpose of the present study is to develop in vitro assays for rapid screening of a large number of food samples that contain components that prevent tumor formation in vivo and to identify the components that contribute to this antitumor effect. Wheat samples representing numerous strains and cultivars were screened for their in vitro ability to kill a human colon cancer cell, CaCo2, in culture by trypan blue dye exclusion assay. Wheat samples were assayed for orthophenolic acid content by use of a colori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…Phenolics present in the whole wheat can act as antibiotics or antioxidants. The presence of the orthophenolics in wheat was correlated significantly with tumour inhibition [25]. The metabolism of lignans (di-phenolics found in whole wheat) has been also been correlated with a reduced risk of breast cancer [26].…”
Section: Cancermentioning
confidence: 99%
“…Phenolics present in the whole wheat can act as antibiotics or antioxidants. The presence of the orthophenolics in wheat was correlated significantly with tumour inhibition [25]. The metabolism of lignans (di-phenolics found in whole wheat) has been also been correlated with a reduced risk of breast cancer [26].…”
Section: Cancermentioning
confidence: 99%
“…Additionally, a study conducted on antitumor activity showed a positive correlation with the orthophenolic content in wheat samples given to Min mice [20]. As a result we investigated the orthophenolic content in juneberries to test for any correlation with the other assays.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…APC Min mice carry truncated adenomatous polyposis coli (APC) and thus spontaneously develop multiple intestinal neoplasia (Min). Drankhan et al (11) applied this model into tumor prevention by feeding wheat bran and found a significant difference in antitumor activity among various wheat cultivars when the fiber contents were equal. As shown in Table 16.3, we compared the SDG contents in four wheat cultivars with antitumor activities in APC Min mice and found a significant correlation between SDG contents and antitumor activities, suggesting lignans may attribute to the observed colon cancer prevention by wheat bran or whole grain products.…”
Section: Plausible Mechanisms Of Lignans For Cancer Preventionmentioning
confidence: 99%